The Political Economy of Trauma: International Humanitarian Law, the Commercialization of Mental Health, and the Unaccounted Casualties of Nigeria’s Counter-Insurgency - Eni Eja Alobo; Egbe Inyang John; Wekekayo Eteng Ekpe; Aji Elemi Eko; Eko Thomas Alobo (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2026)
This paper proposes a transformative integration of Ubuntu philosophy, captured in the phrase Umuntu ngumuntu ngabantu meaning "I am because we are", into the enforcement mechanisms of international humanitarian law (IHL). It argues that the prevailing state centric, individualistic enforcement paradigm faces systemic challenges in contexts of asymmetric warfare, collective violence, and non state actor impunity. Drawing on African communal justice traditions and the theory of Ubuntu Based Collective Responsibility in International Humanitarian Law (UCR IHL), this work explores how principles of communal accountability, restorative justice, and preventive obligations can strengthen global humanitarian governance. Through detailed case studies of African post conflict societies and contemporary asymmetric conflicts, the paper illustrates how UCR IHL can complement rather than replace existing legal frameworks to foster more legitimate, participatory, and sustainable enforcement. Ultimately, it contends that embedding Ubuntu informed mechanisms into IHL enforcement can address persistent gaps in compliance, victim redress, and conflict prevention, particularly in regions where Western legal paradigms lack cultural resonance. The framework represents a significant contribution to the ongoing project of decolonizing international law and making global governance more epistemically inclusive and practically effective.